(untitled) (Rudarsko-geološko-naftni zbornik, 2015)
During the early stages of the Middle Miocene transgression marine biota invaded the newly formed Paratethys Sea. Reefs and reef-like structures particularly flourished with life, supported by the favourable climate conditions. Miocene biogene buildups show a variety of fossil assemblages and lithologic features. The main reef-builders were bryozoans, coralline algae, corals, oysters, vermetids, sponges and serpulids. Water turbidity and depth were major ecological factors controlling the reef biota. Lithofacies types at the studied localities in Northern Croatia show significant similarity with the Upper Langhian (Middle Badenian) of the Leitha Mountains in Austria, but can also be well compared with Miocene to recent reef structures in the Mediterranean. The Miocene reef-like buildups exhibit different porosity rates and other lithological characteristics.